CO2 injection-induced complex cloud-fracture networks in granite at conventional and superhot geothermal conditions. (December 2021) - Pramudyo, Eko; Goto, Ryota; Watanabe, Noriaki; Sakaguchi, Kiyotoshi; Nakamura, Kengo; Komai, Takeshi
Highlights: Carbon dioxide (CO2 ) fracturing of granite for enhanced geothermal system. CO2-injection induced cloud-fracture network in geothermal conditions. Applicability of Griffith failure criterion for CO2 fracturing. Potential advantages and challenges of CO2 fracturing. Abstract: Complex cloud-fracture networks, favorable for enhanced geothermal system reservoir development, were shown to be able to be achieved in granite under superhot geothermal conditions, with temperatures of approximately 400–500 °C, by injecting low-viscosity water at these temperatures. Nonetheless, water utilization has several drawbacks, such as its reactivity with rock-forming minerals. Carbon dioxide (CO2 ), which has a low viscosity similar to that of the low-viscosity water under both superhot and lower-temperature conventional geothermal conditions, is a proposed replacement to overcome these challenges. This low viscosity of CO2 motivates its application to create cloud-fracture networks under various geothermal conditions. The present study, for the first time, demonstrated the formation of cloud-fracture networks in granite under both geothermal conditions through a set of CO2 fracturing experiments conducted from 200 to 450 °C under conventional and true triaxial stress states. The Griffith failure criterion was shown to be applicable for the formation of a cloud-fracture network in both geothermal conditions because it indicated that the fracture network was formed by the stimulation of pre-existing microfractures. The formation of cloud-fracture networks has potential advantages, such as additional fracturing in the presence of sizable natural fractures and a lower risk of induced seismicity; however, CO2 fracturing has the challenge of narrower fracture apertures under conventional geothermal conditions, which should be addressed in future research.